Renal function and clinical outcomes in survivors of out-of-hospital cardiac arrest - Hao-Wei Lee; Ming-Jen Kuo; Pai-Feng Hsu; I-Hsin Lee; Chih-Yu Yang; Teh-Fu Hsu; Chorng-Kuang How; Yenn-Jiang Lin; Chin-Chou Huang (Resuscitation Plus)
Background: Comprehensive studies about renal-function changes in the context of out-of-hospital cardiac arrest (OHCA) have been lacking. Therefore, we investigated the impact of renal function on clinical outcomes among patients with OHCA. Method: This retrospective cohort study enrolled consecutive patients with OHCA between June 2017 and December 2021. Acute kidney injury (AKI) was defined based on the “Kidney Disease: Improving Global Outcomes (KDIGO)” guidelines. AKI recovery was defined as a decrease in serum creatinine below the level determined in the definition of AKI. Clinical outcomes included neurological outcomes and all-cause mortality. Result: A total of 258 patients were enrolled, including 35 patients with underlying end-stage renal disease (ESRD). Among patients without ESRD, 82.5% developed AKI, of which 31.0% achieved AKI recovery, while 61.0% were discharged with impaired renal function. Multivariable analysis using regression models revealed that unfavorable neurological outcomes at discharge and higher mortality at 2 years were associated with AKI (odds ratio [OR] 7.684, 95% confidence interval (CI) 2.683–22.010, P < 0.001; hazard ratio [HR] 2.159, 95% CI 1.272–3.664, P = 0.004), AKI without recovery (OR 5.275, 95% CI 2.049–13.583, P < 0.001; HR 5.470, 95% CI 3.304–9.862, P < 0.001), and impaired pre-discharge renal function (OR 3.164, 95% CI 1.442–6.940, P = 0.004; HR 2.876, 95% CI 1.861–4.443, P < 0.001). Compared to those without ESRD, patients with underlying ESRD had similar neurological outcomes and mortality. Conclusion: AKI, AKI without recovery, and impaired pre-discharge renal function were significantly correlated with worse clinical outcomes in OHCA among patients without ESRD, while underlying ESRD did not lead to worse clinical outcomes.